Intergenerational demographic risk-sharing properties of current social security systems in closed economies and open economies. - Wang, Jingyi. (2012)
This paper examines the risk-sharing properties of two major social security systems, the Pay-as-You-Go (PAYGO) Defined Benefit (DB) systems and the pre-funding systems, in both closed and open economies. An Overlapping Generations (OLG) model is constructed to formulate consumer’s saving and consumption behaviors and examine the risk-sharing properties between two consecutive generations in a closed economy. Following which, we extend our analysis into an open economy context by introducing a static external economy.